An Appraisal of the Legal and Institutional Framework on Digital Taxation in Cameroon - Lillian Efenge Ikundi (Studies in Law and Justice, 2025)
This work explores the legal and institutional framework governing digital taxation in Cameroon. In recent years, digital economy growth has significantly impacted global tax regimes, prompting countries to adapt their fiscal policies to the rapidly evolving sector. Cameroon, as part of its modernization efforts, has begun addressing the challenges of taxing digital platforms and services. This analysis evaluates the current legal provisions, including relevant national laws, tax policies, and their alignment with international standards. It also examines the institutional structures responsible for implementing digital tax laws, such as tax authorities, regulatory bodies, and their coordination with international organizations. Through a review of existing legislation, administrative practices, and regional harmonization efforts, the study identifies key strengths and gaps in the framework. It discusses challenges such as digital service taxation, cross-border transactions, and the difficulty in applying traditional tax models to intangible digital goods and services. Additionally, the appraisal suggests potential reforms and strategies for enhancing the effectiveness of digital taxation in Cameroon, including capacity building for institutions and alignment with global best practices, especially in relation to OECD guidelines on digital taxation. Ultimately, this paper underscores the importance of a robust, transparent, and adaptable digital taxation framework for Cameroon to ensure fair revenue collection, support digital economy growth, and attract foreign investment while mitigating risks of tax avoidance and evasion.